Implementasi Perangkat Gateway Untuk Pengiriman Data Sensor Dari Lapangan Ke Pusat Data Pada Jaringan Wireless Sensor Network Berbasis Perangkat nRF24L01 - Tsany Afif; Adhitya Bhawiyuga; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Internet of Things (IoT) is currently developing technology. Wireless Sensor Network (WSN) is one of technology that use IoT scenario. In the implementation of WSN concept there is constraint on the limited resources that they have. Limited resources cause WSN data processing need to be handled in other systems such as data center. Therefore, to connect communication between sensor node and the data center, gateway device is needed. In this research gateway device will be implemented to bridging communication between sensor nodes and data centers. Communication between gateway and sensor nodes can use the nRF24L01 module which has advantages in low power consumption and supports RF24Mesh protocol which can be applied to wireless sensors. Communication between the gateway and data center can use the MQTT protocol, where this protocol is suitable for devices with limited resources and low bandwidth. The successful rate performance of the gateway built with the nRF24L01 wireless communication module show that the gateway performance at 20 meters distance with 50 Byte packet size and 1 second delay packet delivery has the best performance. Delivery at 30 meters distance and 150 Byte packet size cannot be done because exceeding the distance range and the packet size.